IMPLEMENTASI TEKNIK PERBANYAKAN LEGUME COVER CROP SEBAGAI INOVASI REGENERATIVE AGRICULTURE UNTUK PEMULIHAN KESUBURAN TANAH PADA PERKEBUNAN KELAPA SAWIT - Muhammad Nuriman; Muhamad Noor Azizu; Dendy Detafiano Prakasa Afner; Muhammad Munawir; Adung Sudirman; Albertus Tjiu (Universitas Negeri Makassar, 2026)
Smallholder oil palm plantations established on Ultisols commonly face constraints related to low organic matter content and limited permanent ground cover vegetation, resulting in increased risks of soil degradation. This community service program aimed to enhance farmers’ capacity to propagate and implement Legume Cover Crops (LCC) as a regenerative agriculture innovation in smallholder oil palm plantations. The program was conducted with the Rimba Harapan Farmer Cooperative in Sintang Regency, West Kalimantan, Indonesia, using a Participatory Rural Appraisal (PRA) approach combined with field demonstrations, hands-on practice, and technical assistance. Vegetative propagation techniques were applied using the split-cane cutting method for Mucuna bracteata and stem cuttings for Arachis pintoi, followed by field implementation in dead-row interspaces of 11-year-old mature oil palm plantations (TM 11). Monitoring conducted 21–30 days after propagation showed that Mucuna bracteata achieved a survival rate of 90%, whereas Arachis pintoi exhibited a survival rate of 40% due to drought stress during the early establishment phase. The implementation of LCC in dead-row interspaces demonstrated potential to improve vegetation cover, maintain soil moisture, suppress weed growth, and reduce soil erosion and nutrient losses in smallholder oil palm plantations. The program indicates that simple vegetative propagation techniques can be effectively adopted by farmers and may support the long-term implementation of regenerative agriculture practices in sustainable smallholder oil palm production systems.